PERILAKU SISTEM STRUKTUR ATAP PADA PENDHAPA TRADISIONAL JOGLO TERHADAP PENGARUH BEBAN GEMPA Studi Kasus Bangsal Trajumas - , Dyah Hendrawati ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Traditional Joglo building is one of the development of the Java basic types of house, namely type tajug. Characteristic Joglo roof can be seen from the roof in the form of a triangle and the area of a trapezium with different tilt angles. Form of a joint between the roof as lambang sari and lambang gantung. System structure joglo traditionally divided into the roof structure, the main structure and the follower structure. Roof structure consists of : cover the roof, rafters, molo, ander, dudur and beam, while the main structure is composed of : umpak, saka guru and brunjung. Follower structure, such as the expansion of space with a roof which joins the lambing sari or lambing gantung. Tectonic earthquakes are a natural phenomenon that is becoming one of the challenges for the traditional architecture of the building on the past or the present. System construction and configuration of existing structural systems capable of generating behavior that is responsive to the earthquake. This study aims to determine the behavior of the structures that occur in the roof structure by reviewing the relationship between elements using special construction methods to produce a system that is able to respond to earthquake loads. The study was conducted by means of direct observation and measurement of the existing building, including: building dimensions, dimensions and elements of the work load. The data that is then analyzed by studying the mechanical specifications that occur in the relationship between elements which then dikomparasikan magnitude earthquake magnitude. The method used is based on problems with the method of qualitative descriptive analysis. The roof of the building has a traditional joglo hierarchy of elements and different methods of construction of modern buildings. This makes the system structure of the roof structure has a different behavior of the main structure of the system. In traditional roof joglo not merely serve as a building pelidung alone but has the ability to stabilize the overall building form. The results of this study are expected to provide an explanation of traditional Joglo roof behavior in detail so that it can be a material consideration and learning to be applied to similar buildings when performing maintenance, repair and reconstruction. Keywords: behavior of the structure, roof joglo, hierarchy of elements, construction methods,earthquake